Special issue: computer-based performance assessment of problem solving (Computers in Human Behavior)
A special issue on computer-based performance assessment of problem solving. Topics discussed include a conceptual framework for the assessment of problem solving using computer-based techniques; the components required to assess student problem solving in technology environments; using multimedia in large-scale computer-based testing programs; the ability of artificial neutral network technologies to generate performance models of complex problem-solving tasks; the reliability and validity of a computer-based knowledge mapping system to measure content understanding; an evidence-centered approach to designing a computer-based performance assessment of problem solving; the use of networked simulation to assess problem solving by military tactical teams; computer-based performance assessments as a solution to the narrow measurement and reporting of problem solving; fairness issues in a computer-based architectural licensure examination; an event-based approach to training team problem solving skills; the use of computer-based, networked collaborative knowledge mapping system to measure teamwork skills; the effects of test item format on worry and self-efficacy during a computerized, high-stakes certification exam; and effects of expertise on state worry and state self-efficacy during a a computerized job-related certification test.